Sperm DNA Integrity and Male Fertility in Farm Animals: A Review - Kumaresan, Arumugam; Das Gupta, Mohua; Datta, Tirtha Kumar; Morrell, Jane M. (Frontiers in Veterinary Science, 2020)
The accurate prediction of male fertility is of major economic importance in the animal breeding industry. However, the results of conventional semen analysis do not always correlate with field fertility outcomes. There is evidence to indicate that mammalian fertilization and subsequent embryo development depend, in part, on the inherent integrity of the sperm DNA. Understanding the complex packaging of mammalian sperm chromatin and assessment of DNA integrity could potentially provide a benchmark in clinical infertility. In the era of assisted reproduction, especially when in-vitro fertilization or gamete intrafallopian transfer or intracytoplasmic sperm injection is used, assessment of sperm DNA integrity is important because spermatozoa are not subjected to the selection process occurring naturally in the female reproductive tract. Although sperm DNA integrity testing measures a significant biological parameter, its precise role in the infertility evaluation in farm animals remains unclear. In this review, the earlier findings on sperm DNA integrity in relation to male fertility are compiled and analyzed. Furthermore, the causes and consequences of sperm DNA damage are described, together with a review of advances in methods for detection of sperm DNA damage, and the prognostic value of sperm DNA quality on male fertility.